COMPETITIVENESS OF A FAMILY BUSINESS WAYS TO IMPROVE - Yuldashev Doniyor; Nishonboyev Doniyor (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The introduction of the previously described ways and mechanisms to increase the competitiveness of the family business in our country will ultimately ensure the rapid development of this sector and create the basis for increasing the level of use of its economic opportunities.